Behavior and Survival of Stocked Trout in Southern Appalachian Mountain Streams. Issue 1 (25th October 2018) - Flowers, H. Jared; Kwak, Thomas J.; Fischer, Jesse R.; Cope, W. Gregory; Rash, Jacob M.; Besler, Douglas A.
Abstract: Stocking of trout to support recreational fisheries is a common practice among state and federal agencies to meet angling and harvest demands. Success of stocking efforts relies upon fish behavior and survival to maximize the availability of fish to anglers. We quantitatively described the movement behavior and survival of stocked Brook Trout Salvelinus fontinalis, Brown Trout Salmo trutta, and Rainbow Trout Oncorhynchus mykiss in three southern Appalachian Mountain streams in western North Carolina, USA, that were managed under delayed harvest regulations. Hatchery trout were tagged with a combination of PIT tags and radio transmitters (radio tags); stocked into "Delayed Harvest Trout Waters" of the North Toe, East Prong Roaring, and Little rivers; and monitored during the catch‐and‐release season from October to June. Assessed according to river and species, 19–65% of trout emigrated from the delayed harvest study reaches, while 1–29% died within the reaches. The majority of radio‐tagged fish (71%; 59–85% by river) remained within 2 km of the stocking location, whereas 6% migrated over 10 km from the stocking location. Few trout stocked during fall (October and November) were available to anglers the following June due to a combination of migration and mortality. Emigration from delayed harvest study reaches was associated with stocking and high‐flow events. Multi‐state modeling detailed these observations with weekly estimates of migration and survival rates. River‐specific differences in emigration and mortality suggested that emigration was a greater source of trout loss than mortality in all rivers; no pattern related to river size was apparent in emigration, but mortality was greater in small streams. Brook Trout mortality rates were highest among the three species, and large fish of most species showed higher emigration and mortality than catchable‐sized trout. Fisheries managers can apply our results to alter stocking regimes so as to enhance the efficiency of stocking and the acclimation of stocked trout to instream environments.